Design of Photonic Phased Array Switches Using Nano Electromechanical Systems on Silicon-on-insulator Integration Platform - Hussein, Ali Abdulsattar (Université d'Ottawa / University of Ottawa, 2014)
This thesis presents an introduction to the design and simulation of a novel class of integrated photonic phased array switch elements. The main objective is to use nano-electromechanical (NEMS) based phase shifters of cascaded under-etched slot nanowires that are compact in size and require a small amount of power to operate them. The structure of the switch elements is organized such that it brings the phase shifting elements to the exterior sides of the photonic circuits. The transition slot couplers, used to interconnect the phase shifters, are designed to enable biasing one of the silicon beams of each phase shifter from an electrode located at the side of the phase shifter. The other silicon beam of each phase shifter is biased through the rest of the silicon structure of the switch element, which is taken as a ground. Phased array switch elements ranging from 2×2 up to 8×8 multiple-inputs/multiple-outputs (MIMO) are conveniently designed within reasonable footprints native to the current fabrication technologies. Chapter one presents the general layout of the various designs of the switch elements and demonstrates their novel features. This demonstration will show how waveguide disturbances in the interconnecting network from conventional switch elements can be avoided by adopting an innovative design. Some possible applications for the designed switch elements of different sizes and topologies are indicated throughout the chapter. Chapter two presents the design of the multimode interference (MMI) couplers used in the switch elements as splitters, combiners and waveguide crossovers. Simulation data and design methodologies for the multimode couplers of interest are detailed in this chapter. Chapter three presents the design and analysis of the NEMS-operated phase shifters. Both simulations and numerical analysis are utilized in the design of a 0º-180º capable NEMS-operated phase shifter. Additionally, the response of some of the designed photonic phased array switch elements is demonstrated in this chapter. An executive summary and conclusions sections are also included in the thesis.
Keywords: integrated photonic phased array switches; photonic integrated circuits; nano-electromechanical systems; NEMS-operated phase shifters; Mach-Zehnder interferometers; multimode interference couplers; wavelength division multiplexing; broadband phased array switches; response of phased array switches